Government Spending and the Taylor Principle - Gisle James Natvik (Norges Bank, 2006)
This paper explores how government size affects the scope for equilibrium indeterminacy in a New Keynesian economy where part of the population live hand-to-mouth. I find that in this framework, a larger public sector may widen the scope for self-fulfilling prophecies to occur. This takes place even though taxes serve to reduce swings in current income. In general, government provision of goods that are Edgeworth substitutes for private consumption tend to narrow the scope for indeterminacy, while government goods that are Edgeworth complements for private consumption increase the problem of indeterminacy. Hence monetary policy should be conducted with an eye to the amount and composition of government consumption.
hdl:11250/2498362
Keywords: E32; E52; E63; 330; Taylor principle; public expenditures; fiscal policy rules; rule-of-thumb consumers